Early hydration of cementitious systems accelerated by aluminium sulphate: Effect of fine limestone. (August 2020) - Briendl, Lukas G.; Mittermayr, Florian; Baldermann, Andre; Steindl, Florian R.; Sakoparnig, Marlene; Letofsky-Papst, Ilse; Galan, Isabel
Abstract: The early hydration of cementitious systems accelerated by an alkali-free aluminium sulphate based product was investigated in the presence and absence of fine limestone. The results show that the first seconds after the accelerator is added to the wet mix play a key role: Simultaneously to the massive ettringite formation, the Al2 (SO4 )3 accelerator favours the dissolution of the major cement clinker phase alite and thereby leads to an oversaturation of the pore solution with respect to calcium-aluminium-silicate-hydrates (C-A-S-H) and consequently the precipitation of nuclei of these phases. The surface of the limestone powder acts as an ideal substrate for these nuclei, which are the foundation for an outstanding early-strength-giving effect a few hours later.